Advances in organic thermoelectric materials and devices for smart applications. (1st June 2021) - Zhao, Yue; Liu, Liyao; Zhang, Fengjiao; Di, Chong‐an; Zhu, Daoben
Abstract: Organic thermoelectric (OTE) materials have been considered to be promising candidates for large area and low‐cost wearable devices owing to their tailorable molecular structure, intrinsic flexibility, and prominent solution processability. More importantly, OTE materials offer direct energy conversion from the human body, solid‐state cooling at low electric consumption, and diversified functions. Herein, we summarize recent developments of OTE materials and devices for smart applications. We first review the fundamentals of OTE materials from the viewpoint of thermoelectric performance, mechanical properties and bionic functions. Second, we describe OTE devices in flexible generators, photothermoelectric detectors, self‐powered sensors, and ultra‐thin cooling elements. Finally, we present the challenges and perspectives on OTE materials as well as devices in wearable electronics and fascinating applications in the Internet of Things. Abstract : Organic thermoelectric (OTE) materials have been considered to be promising candidates for large area and low‐cost smart electronics. This review summarizes the fundamentals and recent developments of OTE materials and devices for flexible generators, photothermoelectric detectors, self‐powered sensors, and ultra‐thin cooling elements. Challenges and perspectives are also proposed for OTE‐based wearable electronics and the Internet of Things.